Analisis Yuridis Penanganan Pasien Peserta BPJS Kesehatan: Studi Kasus Di RSUD Kabupaten Bima - Nurmawaddah Nurmawaddah; Edy Yanto; Anies Prima Dewi; Roni Fardiillah (Yayasan Pendidikan Kardin Assidiq, 2025)
The implementation of the National Health Insurance (JKN) in Indonesia depends significantly on the adherence of healthcare facilities to Law Number 24 of 2011, which governs the Social Security Administering Body (BPJS). This study aims to analyse how well the patient handling procedures at the Regional General Hospital (RSUD) of Bima Regency align with legal requirements while identifying the obstacles to effective service delivery. Using a normative-empirical legal research method, this study combines a statutory approach—specifically examining Law No. 40 of 2004 and Law No. 24 of 2011—with empirical data on implementation challenges. The findings indicate a divergence in legal compliance. The hospital meets standards regarding its physical facilities and upholds principles of non-discriminatory treatment. However, significant structural gaps persist. First, the dissemination of information about BPJS benefits is inconsistent, resulting in widespread public unawareness that contradicts the legal obligation for comprehensive socialisation. Second, there is a critical shortage of human resources, particularly specialist doctors, resulting in long waiting times and lower patient satisfaction. In conclusion, although the hospital's infrastructure complies well with legal standards, the full realisation of the Social Security Law is hindered by a lack of human capital and insufficient public communication strategies.